Impact of oil palm on land cover and land use in Kalangala and Buvuma – trends and future predictions - Nangendo, G.; Namuwaya, S.; Timbuka, M. (Ecological Trends Alliance Texts, 2019)
The introduction and expansion of oil palm on Uganda’s Lake Victoria islands show that on Kalangala, oil palm has replaced much of natural forest, while on Buvuma it will replace subsistence farming and therefore have major impacts on food production and community livelihoods. Adequate and timely land-use planning should have been applied to ensure food security and minimize environmental impacts, and should be emphasized in the future.